2002
DOI: 10.1210/jc.2001-011535
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin in Girls: Relationship to Obesity, Hyperinsulinemia, and Puberty

Abstract: In adults with impaired glucose tolerance (IGT) and obesity (OB), an elevated proinsulin (PI) is predictive of type 2 diabetes mellitus (DM) and precedes the diagnosis by 5-20 yr. In type 2 DM, the PI is disproportionately elevated, i.e. increased PI/insulin ratio (PI/I). Few studies have evaluated PI in children at risk for type 2 DM. In the face of the current epidemic, we evaluated the relationship of PI and PI/I to IGT, insulin resistance (IR) defined by homeostasis model of assessment (HOMA), degree of OB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…The higher proinsulin-to-insulin ratio and percentage of proinsulins in girls in our study could theoretically be due to either decreased clearance or differences in conversion of proinsulin to insulin (19). Higher proinsulin(s) have been found in neonates previously (11,12), and this may be part of the neonatal transition reflecting immaturity of the fetal ␤-cell and/or ␤-cell secretory granule.…”
Section: Relationships With Mode Of Deliverymentioning
confidence: 55%
See 1 more Smart Citation
“…The higher proinsulin-to-insulin ratio and percentage of proinsulins in girls in our study could theoretically be due to either decreased clearance or differences in conversion of proinsulin to insulin (19). Higher proinsulin(s) have been found in neonates previously (11,12), and this may be part of the neonatal transition reflecting immaturity of the fetal ␤-cell and/or ␤-cell secretory granule.…”
Section: Relationships With Mode Of Deliverymentioning
confidence: 55%
“…Our finding that insulin and insulin propeptides in cord blood are higher in girls than in boys is consistent with an intrinsic difference between the sexes, which is unlikely to be determined by environmental factors. Other research has suggested that in childhood, girls are more insulin resistant than boys with higher insulin and proinsulin concentrations and more adipose tissue from age Ն5 years, and these differences could not be explained by other known determinants of insulin concentrations (1,3,4,6,19). We think that because girls are born smaller (lighter and shorter), with greater skinfold thickness, and in the presence of higher insulin concentrations than boys but with no corresponding increase in cord glucose concentrations, they are intrinsically more insulin resistant.…”
Section: Relationships With Mode Of Deliverymentioning
confidence: 99%
“…Fasting insulin, HOMA, and QUICKI have been shown to correlate with euglycemichyperinsulinemic clamp studies and have been used previously in children and adolescents (12,13). WFH and %BF by BIA and DEXA were used as measures of the severity of obesity.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Consistent with the present study, increased proinsulin levels with increasing insulin resistance in obese girls suggested that elevated proinsulin concentrations reflect increased ␤-cell output proportional to the elevated insulin concentrations in this group and not a defect in proinsulin processing or secretion. 8 The use of acanthosis nigricans as a predictive marker of hyperinsulinemia has become a common practice. Previous studies have associated the presence of acanthosis nigricans with high insulin levels, thus identifying a subgroup believed to be at greater risk for T2DM.…”
Section: Commentmentioning
confidence: 99%